ANALISIS KEPUASAN KONSUMEN PEDAGANG LANGKITANG KAKI LIMA DI KAWASAN OBJEK WISATA PANTAI PADANG - Hafrizal Okta Ade Putra (Politeknik Negeri Padang, 2017)
The purpose of this research is to know and analyze, (1) the influence of food quality to the satisfaction of the merchant of Langkitang in Padang beach resort area; (2) the influence of price to the satisfaction of the merchant of Langkitang in Padang beach resort area, 3) the influence of food quality and price simultaneously to the satisfaction of merchant consumers Langkitang pavement in the area of Padang Beach tourist attraction. Population in this research is all consumer of Langkitang merchant of pavement in Padang beach resort area. The number of samples in this study is 100 respondents which use accidental sampling technique. Based on the result of the research, it can be seen that: (1) The quality of food has a significant effect on the satisfaction of the consumers in the street vendors in Padang Beach tourist area, where t-count 2,685 from t-table 1,661 and significance 0,009 less than level of significant (α ) 0.05. (2) Price has a significant effect to customer satisfaction at Langkitang street vendors in Padang Beach tourist area, where t-count 2,564 > t-table 1,661 and significance 0.012 < level of significant (α) 0,05. (3) The quality of food and the price simultaneously have a significant effect on the satisfaction of the consumers on the street vendors in Padang Beach, where F-count is 19.496 > F-table 3.09 and the significance of 0.000 is < the level of significant (α) 0.05. (4) The coefficient of determination is 0,272, mean than food quality and price influence consumer satisfaction at trader Langkitang pavement in coastal resort area of Padang equal to 27,2%.